Alto Tietê Myrmecology Laboratory reference collection, São Paulo, Brazil: current status and perspectives - Souza-Campana, Débora Rodrigues; Wazema, Claudia T.; Magalhães, Fabricio S.; Silva, Nathalia S.; Nagatani, Victor H.; Suguituru, Silvia S.; Goto, Mariana A.; Morini, Maria Santina C. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Reference collections are important repositories of the biodiversity. They contain representative samples and biological information of specific regions, which can be used to a variety of scientific studies. The collection of the Alto Tietê Myrmecology Laboratory is one of the most important ant regional collections for taxonomic and ecological studies. Currently, it counts with 243 species/morphospecies of ants occurring in different areas of the Atlantic Forest of Alto Tietê (SP). Although it is a small collection, it comes from standardized samplings, which is also true for the entire morphospecies repository. The collection has already generated many publications in different areas of knowledge, and it has also contributed in the training of professionals working in formal and non-formal research and education.
Keywords: Curator; Biological collection; Atlantic Forest; Zoological collections; Conservation